Synthesis of new hydrazide-hydrazone derived from etophenamate and investigation of their antimicrobial activity - GÜRBÜZ, BURÇAK; RAYAMAN, PERVİN; KARAKUŞ, SEVGİ (My University, 2023)
Recently since the emerging resistant strains to antimicrobial agents, the development of original antimicrobial agents in pharmaceutical chemistry has gained great importance. Antibiotic resistance is accepted as one of the greatest threatens against health worldwide. Since 1950s to now it is known that hydrazide-hydrazones have antimicrobial, anticancer, antitubercular, anticonvulsant etc., biological spectrum and biological activity (Polovic et al., 2019). Hydrazone derivatives are used in treatment and involved in the structure of many drugs such as nifuroxazide, nitrofurazone, bisanthren, budralazine, and levosimendan. Etophenamate was chosen as the starting compound to synthesis of 16 novel hydrazide-hydrazones. All of these derivatives were investigated in order to determine their antimicrobial activities. The structures of the synthesized compounds were characterized by IR, 1H-NMR, 13C-NMR, mass spectroscopy and elemental analysis. In this study, the antimicrobial activity of 16 hydrazide-hydrazone derivatives to 4 standard bacterial strains (Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Enterococcus faecalis ATCC 29212) and 4 standard yeast strains (Candida albicans ATCC 90028, Candida glabrata ATCC 90030, Candida parapsilosis ATCC 90018, Candida tropicalis KUEN 1021) was examined by the microdilution method in accordance with the Clinical and Laboratory Standards Institute (CLSI) standards, and the Minimal Inhibitory Concentration (MIC) values of these derivatives were determined. It was found that among these derivatives, 2c (725-0.35µg/ml) and 2p (1000-0.5µg/ml) possed antimicrobial activity against all of the 8 standard microorganism strains.
Keywords: Hydrazid-Hydrazone; Synthesis; Characterization; Antimicrobial activity